Discourse on Occidentalism Studies in Indonesia from The Perspective of Mukti Ali - Abdullah Haq Al Haidary (Islamica: Jurnal Studi Keislaman, 2021)
In the last few decades, religious studies have increasingly excited and attracted the attention of many scholars and groups. Those involved in religious studies are not only religious leaders and scientists in different fields but also politicians and policyholders in various circles. Religious studies is seen as an absolute necessity in the increasingly complex order of modern life. Many experts put their hopes on the intensification and extensification of religious studies in order to create a harmonious social life in this globalized world. In responding to the development of Western thought as a paradigm of religious studies, the concept of occidentalism is very important to be discussed. This article will focus on the discussion of occidentalism, specifically from the perspective of Mukti Ali who in the 1970s served as the Minister of Religious Affairs. As one of the influential figures in Islamic scholarship in Indonesia, he has contributed to the development and enlightenment of Islamic thought in Indonesia. This article argues that Ali’s concept of occidentalism represents the antithesis towards Western orientalism and the renewal of Islamic studies in Indonesia.